Prospective cohort analysis of cellphone use and emotional and behavioural difficulties in children. Issue 12 (23rd May 2016) - Sudan, Madhuri; Olsen, Jorn; Arah, Oyebuchi A; Obel, Carsten; Kheifets, Leeka
Abstract : Background: We previously reported associations between cellphone exposure and emotional and behavioural difficulties in children in the Danish National Birth Cohort using cross-sectional data. To overcome the limitations of cross-sectional analysis, we re-examined these associations with prospectively collected data. Methods: Based on maternal reports, prenatal and postnatal cellphone exposures were assessed at age 7 years, and emotional and behavioural difficulties were assessed at 7 and 11 years with the Strengths and Difficulties Questionnaire. We used multivariable-adjusted logistic regression models to estimate ORs and 95% CIs relating prenatal exposure and age-7 cellphone use to emotional and behavioural difficulties at age 11 years. Results: Children without emotional and behavioural difficulties at age 7 years, but who had cellphone exposures, had increased odds of emotional and behavioural difficulties at age 11 years, with an OR of 1.58 (95% CI 1.34 to 1.86) for children with both prenatal and age-7 cellphone exposures, 1.41 (95% CI 1.20 to 1.66) for prenatal exposure only, and 1.36 (95% CI 1.14 to 1.63) for age-7 use only. These results did not materially change when early adopters were excluded, or when children with emotional and behavioural difficulties at age 7 years were included in the analysis. Conclusions: Our findings are consistent with patterns seen in earlier studies, and suggest that both prenatal and postnatal exposures may be associated with increased risks of emotional and behavioural difficulties in children.